Surgical Treatment of Acquired Atresia of the External Auditory Ear Canal - Droessaert,Valerie (2017)
Abstract Introduction Acquired atresia of the external auditory canal is characterized by the formation of fibrous tissue in themedial part. The causes include chronic otitis externa, perforated chronic otitis media, postoperative or idiopathic healing problems. Acquired atresia presents with hearing loss and can be associated with otorrhea. Objective We analyzed the results of surgery after six months and two years by checking (1) pre- and postoperative hearing thresholds; (2) presence of otorrhea; and (3) whether a dry and patent ear canal is achieved. Methods We conducted this retrospective study at a tertiary referral center. In total, 27 ears underwent treatment with resection of the fibrotic plug followed by transplantation of a split-thickness skin graft covering the bare bone and tympanic membrane. When necessary, we combined this with a myringoplasty and a (meato-) canalplasty. Results Otorrhea was present in 59.3% of the patients initially and in 14.8% at six months and 11% at two years postoperative. A dry and patent ear canal was obtained in 55.6% after six months and in 89% of the patients after two years (n = 27). The pure tone average before surgery was 39.1 dBHL (SD = 20 dBHL), at six months 31.4 dBHL (SD = 16.4 dBHL), and at 24 months postop 30.9 dBHL (SD = 17.1 dBHL). We observed a statistically significant improvement of hearing in 63% of the patients at six months (p = 0.005) and in 65% after two years (p = 0.022). Conclusions Treatment of acquired atresia remains a challenge. Using the appropriate surgical technique, including skin-grafting and regular postoperative check-up, rendered excellent results regarding otorrhea and a moderate improvement of hearing was achieved in 65% of the patients after two years.